Equation x^3 + y^3 + z^3 = 1

 
 
x^3 \; + y^3 \; + \; z^3 \; = \; k

For   k = 1
 

9^3 + 10^3 - 12^3 = 1
(-6)^3 + (-8)^3 + 9^3 = 1

4528^3 + 3753^3 + (-5262)^3 = 1
(-3230)^3 + 3753^3 + (-2676)^3 = 1

(837313192)^3 + (693875529)^3 + (-972979926)^3 = 1
(-597125510)^3 + (693875529)^3 + (-494833692)^3 = 1

154817534664928^3 + 128296197510633^3 + (-179902042398942)^3 = 1
(-110407312449710)^3 + 128296197510633^3 + (-91493760027396)^3 = 1

28625452523638639192^3 + 23721710326627098249^3
   + (-33263527834506644646)^3 = 1

(-20414091256729259030)^3 + 23721710326627098249^3
   + (-16917013241050678572)^3 = 1

5292788920560919574752528^3+4386096795844401014486313^3
   + (-6150359769364707539403822)^3 = 1

(-3774524645076319223584190)^3+4386096795844401014486313^3
   + (-3127921914152294606624916)^3 = 1

 

To be continued
 
 

 
 
 
 
 
 
 
 
 
 
 
 
 
 
 

Advertisements

About benvitalis

math grad - Interest: Number theory
This entry was posted in Number Puzzles and tagged . Bookmark the permalink.

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s